Landslide-controlled soil erosion rate in the largest tableland on the Loess Plateau, China. Issue 9 (20th October 2020) - Kou, Pinglang; Xu, Qiang; Yunus, Ali P.; Liu, Jie; Xu, Yali; Wang, Cuilin; Li, Huajin; Wei, Yong; Dong, Xiujun
Abstract: Hillslopes in the steep mountainous terrains are eroded by landslides, however the quantitative characterization of the interaction between the soil erosion and landslide is rare. Here, taking the largest tableland in the Loess Plateau of China as an example, we calculated the area and volume of 5, 420 shallow loess landslides and compared these against the Chinese Soil Loss Equation (CSLE) derived soil erosion rate of 15 sub-catchments. The results on the spatial variability of soil erosion suggest that the average soil erosion modulus in the study area is 50.54 tons·ha −1 ·year −1, but the value varies widely across the whole research area. Overall, soil erosion is more severe in the north, which is similar to the distribution of landslide scars extracted from Google imagery. The volume of the landslides in the northern watershed was approximately 4-fold that of the landslides in the southern watershed. Our analysis reveals a satisfactory linear fitting result (R 2 = 0.68) between the area of landslides and soil erosion. Based on the results, we believe that restoring vegetation cover in landslide scars should become the most urgent action to mitigate soil erosion.